2016
DOI: 10.1242/jcs.186247
|View full text |Cite
|
Sign up to set email alerts
|

CCN6 regulates mitochondrial function

Abstract: Despite established links of CCN6, or Wnt induced signaling protein-3 (WISP3), with progressive pseudo rheumatoid dysplasia, functional characterization of CCN6 remains incomplete. In light of the documented negative correlation between accumulation of reactive oxygen species (ROS) and CCN6 expression, we investigated whether CCN6 regulates ROS accumulation through its influence on mitochondrial function. We found that CCN6 localizes to mitochondria, and depletion of CCN6 in the chondrocyte cell line C-28/I2 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 67 publications
4
45
0
Order By: Relevance
“…Previously, we demonstrated that CCN6 regulates the production of reactive oxygen species (ROS) and localizes to mitochondria. 20,21 In the current study, we demonstrated using chondrocyte lines that CCN6 controls the assembly and activity of mitochondrial respiratory Complex I, an entity of 45 subunits present also in the form of Super Complexes, and crucial for mitochondrial electron transport. [22][23][24] The level of cell associated CCN6 protein and its mitochondrial distribution are important for the regulation of mitochondrial respiratory complex assembly and activity.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…Previously, we demonstrated that CCN6 regulates the production of reactive oxygen species (ROS) and localizes to mitochondria. 20,21 In the current study, we demonstrated using chondrocyte lines that CCN6 controls the assembly and activity of mitochondrial respiratory Complex I, an entity of 45 subunits present also in the form of Super Complexes, and crucial for mitochondrial electron transport. [22][23][24] The level of cell associated CCN6 protein and its mitochondrial distribution are important for the regulation of mitochondrial respiratory complex assembly and activity.…”
Section: Introductionmentioning
confidence: 68%
“…Such a detailed concept of mitochondrial respiration by CCN6 remained unexplained in our previous study although we observed closer association of mitochondria with the ER in CCN6 depleted cells. 21 Generation of a CCN6 knock out cell line for evaluating how essential CCN6 is for mitochondrial function was difficult. However, we generated cell lines expressing CCN6 C-terminal truncation mutants similar to those linked with PPRD so as to decipher the effect of these mutants on mitochondrial function and integrity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Potential roles of CCNs acutely in regulation of macronutrients of protein, lipids and carbohydrate, and cellular downstream pathways, for example of glucose metabolism, have been minimally examined. Of much intrigue, a recent abstract identified CCN6 as protein that localizes to mitochondria and may act as a regulator mitochondrial electron transport in eukaryotic cells (Patra et al 2017). At the same recent international CCN Workshop, it was reported that in chondrocytes CCN2 and CCN3 may differentially regulate glycolysis in a sub-acute time course (Kubota et al 2017).…”
Section: Ccns Metabolic Disease and Future Directionsmentioning
confidence: 99%